Do Farmers Block the Development of Poland? - Maria Halamska (Studia Regionalne i Lokalne, 2017)
Polish farmers, including rural pensioners, make up a social group which is difficult to define. It is a diversified population, dominated (in numbers) by ‘quasi-farmers’ – those who run small subsistence farms and do not sell their products in the market. This category has many negative, economic, social and psychological features. In their political choices, farmers often choose to support populist agrarian parties. The author, referring to her earlier concept of ‘blocking development’ and ‘moderating changes’, describes the political mechanisms of slowing down the reforms, triggered by a broadly understood community of Polish farmers.